2009
DOI: 10.1002/bies.200900026
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements and an epigenetic basis for punctuated equilibria

Abstract: Evolution is frequently concentrated in bursts of rapid morphological change and speciation followed by longterm stasis. We propose that this pattern of punctuated equilibria results from an evolutionary tug-of-war between host genomes and transposable elements (TEs) mediated through the epigenome. According to this hypothesis, epigenetic regulatory mechanisms (RNA interference, DNA methylation and histone modifications) maintain stasis by suppressing TE mobilization. However, physiological stress, induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
136
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 118 publications
7
136
0
1
Order By: Relevance
“…But by the end of the decade, he and his colleagues had concluded that because cytosine methylation is predominantly found in TEs, methylation was more likely to represent a nuclear defense system that had evolved precisely to "control" the destructive potential of "parasitic sequences," mostly transposons and retrotransposons (5,29). This view was widely accepted, and transposons are today almost universally referred to as "invaders," "parasites," or "parasitic sequences" (30)(31)(32)(33).…”
mentioning
confidence: 99%
“…But by the end of the decade, he and his colleagues had concluded that because cytosine methylation is predominantly found in TEs, methylation was more likely to represent a nuclear defense system that had evolved precisely to "control" the destructive potential of "parasitic sequences," mostly transposons and retrotransposons (5,29). This view was widely accepted, and transposons are today almost universally referred to as "invaders," "parasites," or "parasitic sequences" (30)(31)(32)(33).…”
mentioning
confidence: 99%
“…For example, in the Monodelphis research the investigators noted that much of the evolutionary innovation distinguishing metatherian from eutherian mammals was not due to differentiation in coding sequences but was instead due to differences in noncoding DNA and that TEs are a ''major creative force'' in mammalian evolution. Furthermore, one recent publication provided strong arguments suggesting that increases in transposable element activity in response to physiological stress may provide the foundation for the punctuated equilibrium model of evolutionary change (Zeh et al 2009). …”
mentioning
confidence: 99%
“…One of these is Copia-like retrotransposon which is distributed over all oil palm genome (Castilho et al, 2000). Transposon could be activated by biotic and abiotic stress (Zeh et al, 2009). Present result indicated that the transposon was activated in oil palm genome due to dry periods exist during the year.…”
Section: Resultsmentioning
confidence: 66%